Oorlog, ongelijkheid en overheidsfinanciën: oorzaak of gevolg? - Feenstra, Alberto (TSEG - The Low Countries Journal of Social and Economic History, 2025)
This review highlights three aspects of public finance to discuss ’t Hart’s claims about the relationship between warfare and inequality during the Dutch Golden Age. First it questions independence as an explanation for the willingness to pay high taxes. Secondly, it downplays the importance of Holland’s provincial credit in financing the Eighty Years’ War. Third, it questions the claim that the province of Holland was overburdened in the collective costs of the war. For each of these aspects, ‘t Hart attributes too little importance to late medieval economic developments.